Investigation Of Vitamin B12-Modified Amphiphilic Sodium Alginate Derivatives For Enhancing The Oral Delivery Efficacy Of Peptide Drugs - Long L (Dove Medical Press, 2019)
Lingli Long,1,2,* Minghua Lai,3,* Xuhong Mao,4 Jiahao Luo,3 Xin Yuan,2 Li-Ming Zhang,4 Zunfu Ke,5 Liqun Yang,3 David YB Deng1,2 1Department of Research Center of Translational Medicine, The First Affiliated Hospital, Sun Yat-sen University, Guangzhou 510080, People’s Republic of China; 2Department of Scientific Research Center and Orthopedic, The Seventh Affiliated Hospital, Sun Yat-sen University, Shenzhen 518107, People’s Republic of China; 3Department of Polymer and Material Science, School of Chemistry, Key Laboratory for Polymeric Composite and Functional Materials of Ministry of Education, Guangdong Provincial Key Laboratory for High Performance Polymer-based Composites, Sun Yat-sen University, Guangzhou 510275, People’s Republic of China; 4Faculty of Materials Science and Engineering, Sun Yat-sen University, Guangzhou 510275, People’s Republic of China; 5Department of Pathology, The First Affiliated Hospital, Sun Yat-sen University, Guangzhou 510080, People’s Republic of China*These authors contributed equally to this workCorrespondence: David YB DengDepartment of Research Center of Translational Medicine, The First Affiliated Hospital, Sun Yat-sen University, Guangzhou 510080, People’s Republic of ChinaEmail dengyub@mail.sysu.edu.cnLiqun YangDepartment of Polymer and Material Science, School of Chemistry, Key Laboratory for Polymeric Composite and Functional Materials of Ministry of Education, Guangdong Provincial Key Laboratory for High Performance Polymer-based Composites, Sun Yat-sen University, Guangzhou 510275, People’s Republic of ChinaEmail yanglq@mail.sysu.edu.cnPurpose: Peptide drugs have been used in therapy various diseases. However, the poor bioavailability of peptide drugs for oral administration has limited their clinical applications, on account of the acidic environment and digestive enzymes inside the human gastrointestinal tract. To enhance stability in the human gastrointestinal tract, bioavailability, and targeted drug delivery of peptide drugs through oral administration, a vitamin B12-modified amphiphilic sodium alginate derivative (CSAD-VB12) was synthesized.Materials and methods: A vitamin B12-modified amphiphilic sodium alginate derivative (CSAD-VB12) was synthesized via the N,N’-dicyclohexylcarbodiimide active method at room temperature, and then characterized using FTIR and 1H NMR spectroscopy. Insulin was used as a model peptide drug and the insulin-loaded CSAD-VB12 (CSAD-VB12/insulin) nanoparticles with negative zeta potentials were prepared in PBS (pH=7.4). Scanning electron microscopy was used to observe CSAD-VB12/insulin as spherical nanoparticles. The CSAD-VB12 derivatives and CSAD-VB12/insulin nanoparticles displayed nontoxicity towards the human colon adenocarcinoma (Caco-2) cells by CCK-8 test. Caco-2 cell model was used to measure the apparent permeability (Papp) of insulin, CSAD/insulin and CSAD-VB12/insulin. Furthermore, confocal was used to confirm the endocytosis of intestinal enterocytes. Type 1 diabetes mice were used to evaluate the intestinal absorption and retention effect of test nanoparticles.Results: They were observed as spherical nanoparticles in the size of 30–50 nm. The CSAD-VB12 derivatives and CSAD-VB12/insulin nanoparticles displayed nontoxicity towards the human colon adenocarcinoma (Caco-2) cells. Comparing with insulin and the CSAD/insulin nanoparticles, the CSAD-VB12/insulin nanoparticles exhibited higher permeation ability through intestinal enterocytes in the Caco-2 cell model. Oral administration of the CSAD-VB12/insulin nanoparticles to Type 1 diabetic mice yields higher intestinal retention effect, targeted absorption, and outstanding efficacy.Conclusion: CSAD-VB12 derivatives enhance the small intestinal absorption efficacy and retention of peptide by oral administration, which indicated that it could be a promising candidate for oral peptide delivery in the prospective clinical application.Keywords: nanoparticle, insulin, human colon adenocarcinoma cell, small intestinal absorption efficacy